(untitled) (Journal of Enam Medical College, 2014)
Peutz-Jeghers syndrome is a rare autosomal dominant disorder of hamartomatous polyposis of the gastrointestinal tract, with pigmentation around lips and macules on the buccal mucosa that typically manifests itself as recurrent colicky abdominal pain and intestinal obstruction due to intussusception. Here we report a case of a 16-year-old girl who presented with abdominal pain, vomiting and previous history of laparotomy for intussusception. Multiple well demarcated black pigmented macules on lips, perioral region, buccal mucosa, digits, palms and soles were noted. She was diagnosed as a case of Peutz-Jeghers syndrome and managed conservatively. DOI: http://dx.doi.org/10.3329/jemc.v4i3.20958 J Enam Med Col 2014; 4(3): 184-187